A new addition to the Costa Rican flora: Palmorchis nitida (Orchidaceae: Neottieae) is documented from the Osa Peninsula - Bainbridge, Catherine V. (2008)
Palmorchis nitida, previously known from seasonally wet forests of Panama, is reported from the Osa Peninsula in south-west Costa Rica. Notes and figures are provided regarding its natural history and phenology. The variable nature of this species is discussed on the basis of recently collected Costa Rican material.